CAR SALES AND RESERVATION SYS TEM IN THE â€œPT. ARTHASâ€ USING MICROSOFT VISUAL BASIC 6.0 - Awaludin Awaludin; Yudi Irawan Chandra, SKom, MMSI Yudi Irawan Chandra, SKom, MMSI (Jurnal Sistem Informasi, 2008)
This writing describes the system of sales and car reservations at. Arthas is still usinga manual system, so many possibilities of errors. Therefore, the authors provide betteralternatives to make a car reservation system and sales of computerized by usingVisual Basic 6.0 programming language, the authors propose to help process dataprocessing until the preparation of reports.